Clinical Features and Genetic Characteristics of XLID Patients With KDM5C Gene Mutations: Insights on Phenotype–Genotype Correlations From 175 Previous Cases and Identification of a Novel Variant - Mohammad‐Reza Ghasemi; Zahra Esmaeilizadeh; Sahand Tehrani Fateh; Hossein Sadeghi; Saman Bagheri; Farzad Hashemi‐Gorji; Morteza Sheikhi Nooshabadi; Rasoul Madannezhad; Toktam Sadat Tavabe Ghavami; Reza Mirfakhraie; Mohammad Miryounesi (Molecular Genetics & Genomic Medicine)
ABSTRACT Background X‐linked intellectual disability (XLID) is a genetically heterogeneous disorder that results in cognitive impairment and developmental delays. Mutations in the KDM5C gene have been identified as a causative factor in XLID. This study aimed to identify novel variants associated with XLID and to investigate the clinical and genetic characteristics of XLID patients with mutations in the KDM5C gene. This study also conducted a narrative review of the literature to identify key clinical and genetic characteristics of XLID caused by mutations in the KDM5C gene. Study Design Whole‐exome sequencing was performed on the proband's DNA, and Sanger sequencing was used to confirm and analyze the identified variant in a 20‐month‐old male patient with motor and speech delays. Moreover, a comprehensive literature review was conducted to gather previously reported cases, providing insights into the molecular findings and clinical characteristics of this disorder. Results The study identified a novel variant, c.2704C>T:p.Gln902X, located in exon 19 of the KDM5C gene (NM_004187.5) using Whole exome sequencing (WES), highlighting the utility of this approach in identifying rare genetic disorders. The analysis also revealed the variable clinical features associated with KDM5C‐related disorders and identified missense variants as the most prevalent among the reported variants. Conclusions This study provides insights into the clinical and genetic characteristics of XLID associated with KDM5C gene mutations, highlighting the higher manifestation of seizures in males and also addressing the heterogeneity of phenotypes in females. It also identifies a novel pathogenic variant and emphasizes the importance of considering gender‐specific factors and further research to understand the underlying molecular mechanisms. CLINVAR Accession Number SCV004034082